ADSORPTIVE REMOVAL OF FLUORIDE UPDATE FROM AQUEOUS MEDIA BY USING THERMALLY TREATED MARBLE POWDER - Aditya Kumar; Sumit Suman; Abhishek Kumar; Raj Ranjan Kant; Pankaj Kumar (International Educational Journal of Science and Engineering, 2025)
The impacts on the mechanistic feature of marble powder in fluoride extraction were explored by various operating factors. Operating conditions like Initial solute concentration, adsorbent doses and pH of the solution determine the extent of fluoride removal. A model equation from which a percentage removal according to each fluoride removal is determined for a fixed set of experimental conditions. For the maximum fluoride absorption, the contact time, pH & dose respectively were 97.1, 3 hr,7 and 3g respectively at initial concentration 10ppm. Kinetics study showed that marble powder absorbent follows Pseudo second order (R2=0.9701). Itshows good result with intra-particle diffusion (R2=0.6614) kinetics. Marble powder is absorption uses Freundlich isotherm (R2=0.9253) with pH 7 at temp. 305 K and Langmuir, Freundlich, DR-isotherm fits well with R2=0.981, R2=0.9253 and R2=0.9156 respectively. The Freundlich, Langmuir, DR-isotherm are traced for the marble powder. However, the Esvalue of the D-R isotherm 3.535 kJ/mol (mean energy adsorption or bonding energy) is still good fit, indicating physical adsorption.